MAHATMA GANDHI DAN GERAKAN PEREMPUAN DI INDIA - Kamaruddin Salim (Universitas Nasional, 2018)
Ahimsa and Satyagraha were the culmination of Gandhi's struggle. Ahimsa and Satyagraha combine short-term goals with long-term perspectives, more importantly Satyagraha proves the correctness of his method to unite theory with ways of social movement abstinence from violence. Satyagraha proved the strength of the Gandhi method to penetrate the people even though in agrarian areas that were socially and politically underdeveloped, and methods for carrying out a collective approach and education of social movements for women. This is a strategy to instill discipline and active involvement of women in socio-political and economic movements in India. For Gandhi, the involvement of women was an honorable activity for them. Keywords: Ahimsa, Satyagraha, and social movements for women